Voice Security Access Control for Home Door Lock and Appliances - Sathybabu Paiduthaly; Dirman Hanafi; Ayad M. Kwad (Electrical Engineering Department, Faculty of Engineering, Universitas Riau, 2025)
Human voice and speech are among the most natural forms of communication, so extensive research has been conducted to analyze and understand these modalities for various applications. This paper presents a constructive approach to voice security access control hardware. In voice systems, speech is a key interface between humans and machines. The proposed system is designed to facilitate the opening and closing of doors using magnetic locks. It employs a voice integrated circuit (IC) HM2007 and HM 6264 (CMOS SRAM), ensuring a robust design. This system is fully assembled for ease of use and training, allowing users to interact seamlessly with the technology. The testing results indicate that the circuit is capable of accurately detecting voice passwords to unlock the magnetic lock, enhancing security and convenience.